2007
DOI: 10.1159/000108147
|View full text |Cite
|
Sign up to set email alerts
|

Skin Viscoelasticity Displays Site- and Age-Dependent Angular Anisotropy

Abstract: One of the dominant characteristics of skin aging is loss of elasticity. Although the changes in the mechanical properties of the skin over several decades of life are substantial, objective measurements have failed to capture their magnitude thus far. Moreover, the mechanical properties of the skin are not uniform in all directions, and there is a need to understand this angular anisotropy. In this work we present a methodology of documenting the angular anisotropy of skin elasticity with high sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 25 publications
(14 reference statements)
5
89
0
4
Order By: Relevance
“…The time needed by waves to go from the transmitter to the recipient is the measured RRTM parameter expressed in arbitrary units. The resonance running time measurements (RRTM) of acoustical shockwaves propagates differently through the skin according to the state of the elastic fibers and its moisture content (Takema et al, 1994;Hermanns-Lê et al 2001;Ruvolo, Stamatas, Kollias, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The time needed by waves to go from the transmitter to the recipient is the measured RRTM parameter expressed in arbitrary units. The resonance running time measurements (RRTM) of acoustical shockwaves propagates differently through the skin according to the state of the elastic fibers and its moisture content (Takema et al, 1994;Hermanns-Lê et al 2001;Ruvolo, Stamatas, Kollias, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In rigid skin the time for wave spreading will be short, anisotropy and RRTM values smaller (Nizet, Pierard-Franchimont, Pierard, 2001;Verhaegen et al, 2010). Ruvolo, Stamatas and Kollias (2007) and Hermanns-Lê et al (2001) observed that while the minimum RRTM values remained fairly constant for the different age groups, the maximum RRTM values increased with age. Thus, anisotropy is defined as the ratio between maximum and minimum RRTMs and will also increase with age.…”
Section: Corneometermentioning
confidence: 98%
See 3 more Smart Citations